Drug use in Ophthalmology out-patient Department: A Prospective study at a Tertiary Care Teaching Hospital - VI, Prajapati; AK, Yadav (Indian Journal of Pharmacy Practice)
Objective: The present study was undertaken with the aim to study the drug use pattern in ophthalmology out-patient department and to evaluate the drug use for rationality with the help of WHO core drug prescribing indicators and other prescribing parameters. Materials and methods: The study was carried out at ophthalmology out-patient department of a tertiary care teaching hospital. Total 647 patients were included during the study period of six months. The data was collected in a proforma which included the patients' details and the prescriptions details. Results: Prescription analysis showed that the average number of drugs per prescription was 2.23. The maximum number of drugs prescribed, were in the form of eye drops (75.34%), followed by tablets (15.02%), ointments (5.54%), capsules (3.53%), syrups (0.34%), gels (0.13%) and injections (0.10%). Dosage formulation, frequency and duration of therapy recorded were mentioned in 99.7%, 98.97% and 97.44% of prescriptions respectively. The number of antibiotics which were prescribed was 385 (59.50%). The number of patient encounters with anti-inflammatory drugs 130 (20.09%), anti-glaucoma drugs 127 (19.62%), mydriatics 107 (16.53%), artificial tears 89 (13.75%), ocular decongestants 78 (12.05%), steroids 61 (9.42%), anti-histaminic drugs were 60 (9.27%), and those with multi-vitamins were 19 (2.93%). Conclusion: The common prescription writing errors such as duration of therapy, frequency of administration and dosage form were low. This study shows less polypharmacy, use of injections was limited and majority of the drugs were prescribed from the hospital formulary drug list. However prescribing by generic name was very low.
Keywords: Drug use pattern; WHO core drug prescribing indicators; Polypharmacy; Generic name